An Evaluation of the Exhumation Cases Performed in Konya Between 2001 and 2007 - Demirci, Şerafettin; Doğan, Kamil Hakan; Erkol, Zerrin; Deniz, İdris (The Bulletin of Legal Medicine, 2008)
An early and detailed autopsy conducted in forensic death cases will invalidate various allegations and assumptions that could be made after death. It might be necessary to exhume the corpse in order to solve the problems that might arise as a result of the burial of the corpse without performing autopsy or due to inadequate autopsy. The present study aimed at revealing the properties of the exhumation cases whose autopsies were conducted in Konya city center by the Branch Office of Konya Forensic Medicine affiliated to the Institute of Forensic Medicine and in districts of Konya by forensic medicine specialists. For this purpose, records belonging to 42 cases that were exhumed between 2001 and 2007 were examined. The ages of the cases varied between 15 days and 92 years and the average age was found to be 39.8 + 21.8. 29 (69 %) of the cases were male while 13 (31 %) were female. Exhumations were conducted within 1 to 10 days after death in 16 (38.1 %) of the cases. In 12 cases (28.6 %), of which 7 were in the provincial center (35 %) and 5 were in district centers (22.7 %), exhumations had been performed because death certificates had been prepared without the forensic case being reported by the municipal doctor or the hospital authorities. The most common reason for exhumations in districts was in 7 cases (31.8 %) that the forensic cases had been issued death certificates after only death examinations. To reduce the number of exhumations, it will be appropriate to give training to the units issuing death certificates about forensic cases and how to report forensic cases and to the public about not burying their dead without death certificates. Besides, in cases of forensic death, we believe that for a complete and accurate autopsy, all autopsies must be performed in certain centers and by forensic medicine specialists.Keywords: Exhumation, death certificate, death, forensic medicine
Keywords: exhumation; death certificate; death; forensic medicine